2014
DOI: 10.1007/s00775-014-1118-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of transferrin in the distribution of iron, manganese, copper, and zinc

Abstract: The essential role of transferrin in mammalian iron metabolism is firmly established. Integral to our understanding of transferrin, studies in hpx mice, a model of inherited transferrin deficiency, have demonstrated that transferrin is essential for iron delivery for erythropoiesis and in the regulation of expression of hepcidin, a hormone that inhibits macrophage and enterocyte iron efflux. Here we investigate a potential role for transferrin in the distribution of three other physiologic metals, manganese, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Mn is known to complex with other substances in the plasma for transport [29, 30]. Animal studies have found that these plasma transporters used by Mn are also used by other metals such as iron, copper, or zinc [3133]. Thus, co-exposures to these metals could explain some of the within-subject variation in MnP levels due to the competition for transporter binding.…”
Section: Discussionmentioning
confidence: 99%
“…Mn is known to complex with other substances in the plasma for transport [29, 30]. Animal studies have found that these plasma transporters used by Mn are also used by other metals such as iron, copper, or zinc [3133]. Thus, co-exposures to these metals could explain some of the within-subject variation in MnP levels due to the competition for transporter binding.…”
Section: Discussionmentioning
confidence: 99%
“…Mice with decreased circulating Tf display reduced 54 Mn uptake as well as reduced steady-state levels of Mn in the liver 90, 91 , indicating that the Tf-TfR system is important for tissue distribution of Mn. Tf-mediated transport of Mn requires normal function of DMT1, as evidenced by the finding that b/b rats have impaired uptake of Tf-bound Mn, but not free Mn in serum 45 .…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several decades, this mouse line has been used in a multitude of studies. While some have focused on aberrant uptake or distribution of metals such as manganese, aluminum, gallium, cadmium, copper and zinc (Dickinson et al 1996; Radunović et al 1997; Takeda et al 1998; Raja et al 2006; Herrera et al 2014), most studies have employed this mouse model to study transferrin-dependent and -independent pathways of iron metabolism. As such, we will focus on transferrin and iron in this review.…”
Section: Introductionmentioning
confidence: 99%